2023
DOI: 10.3390/polym15173621
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Activity of Biogenic Cinnamic Acid Derivatives in Polypropylene

Jannik Mayer,
René Steinbrecher,
Elke Metzsch-Zilligen
et al.

Abstract: Antioxidants (AOs) from natural resources are an attractive research area, as petroleum-based products can be replaced in polymer stabilization. Therefore, novel esters based on the p-hydroxycinnamic acids p-coumaric acid, ferulic acid and sinapic acid were synthesized and their structure properties relationships were investigated. The structures of the novel bio-based antioxidants were verified using NMR and Fourier-transform infrared (FTIR) spectrometry. The high thermal stability above 280 °C and, therefore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 68 publications
(87 reference statements)
0
1
0
Order By: Relevance
“…Generally, cinnamic acid is composed of simple derivatives, including ferulic acid and p -coumaric acid, and is widely found in plants, including vegetables, fruits, whole grains, and honey [ 125 ]. Past studies have reported that cinnamic acid exhibits a neuroprotective effect [ 126 ], antioxidant [ 127 ], and anti-inflammatory properties [ 128 ]. When utilized in clinical practice, the administration of this compound alone recorded a low bioavailability, which restricts further development in clinical usages for AD [ 125 ].…”
Section: Emerging Potentials Of Thiq Derivatives Via Multi-target The...mentioning
confidence: 99%
“…Generally, cinnamic acid is composed of simple derivatives, including ferulic acid and p -coumaric acid, and is widely found in plants, including vegetables, fruits, whole grains, and honey [ 125 ]. Past studies have reported that cinnamic acid exhibits a neuroprotective effect [ 126 ], antioxidant [ 127 ], and anti-inflammatory properties [ 128 ]. When utilized in clinical practice, the administration of this compound alone recorded a low bioavailability, which restricts further development in clinical usages for AD [ 125 ].…”
Section: Emerging Potentials Of Thiq Derivatives Via Multi-target The...mentioning
confidence: 99%